Biogeography and systematics of endemic island damselflies : The Nesobasis and Melanesobasis (Odonata : Zygoptera) of Fiji (2017)
The study of island fauna has greatly informed our understanding of the evolution of diversity. We here examine the phylogenetics, biogeography, and diversification of the damselfly genera Nesobasis and Melanesobasis, endemic to the Fiji Islands, to explore mechanisms of speciation in these highly speciose groups. Using mitochondrial (COI, 12S) and nuclear (ITS) replicons, we recovered Garli-part maximum likelihood and Mrbayes Bayesian phylogenetic hypotheses for 26 species of Nesobasis and eight species/subspecies of Melanesobasis. Biogeographical patterns were explored using Lagrange and Bayes-Lagrange and interpreted through beast relaxed clock dating analyses. We found that Nesobasis and Melanesobasis have radiated throughout Fiji, but are not sister groups. For Nesobasis, while the two largest islands of the archipelago—Viti Levu and Vanua Levu—currently host two distinct species assemblages, they do not represent phylogenetic clades; of the three major groupings each contains some Viti Levu and some Vanua Levu species, suggesting independent colonization events across the archipelago. Our Beast analysis suggests a high level of species diversification around 2–6 Ma. Our ancestral area reconstruction (Rasp-Lagrange) suggests that both dispersal and vicariance events contributed to the evolution of diversity. We thus conclude that the evolutionary history of Nesobasis and Melanesobasis is complex; while inter-island dispersal followed by speciation (i.e., peripatry) has contributed to diversity, speciation within islands appears to have taken place a number of times as well. This speciation has taken place relatively recently and appears to be driven more by reproductive isolation than by ecological differentiation: while species in Nesobasis are morphologically distinct from one another, they are ecologically very similar, and currently are found to exist sympatrically throughout the islands on which they are distributed. We consider the potential for allopatric speciation within islands, as well as the influence of parasitic endosymbionts, to explain the high rates of speciation in these damselflies. © 2017 The Authors. Ecology and Evolution published by John Wiley & Sons Ltd.